Gerarda prevostiana (Eydoux and Gervais, 1837) (Squamata: Serpentes: Homalopsidae), a New Snake for Borneo - Das, I.; Breuer, H.; Shonleben, S. (Asian Herpetological Research, 2013)
A new record of the homalopsid snake, Gerarda prevostiana is presented from a mangrove-dominated patch in the vicinity of Kampung Bako, Sarawak, East Malaysia, and this comprises the first published record from the Sundaic Island of Borneo. A possible second locality for the species is a ca. 6.68 km site to its northeast, Kampung Buntal, based on an unlocated museum specimen. The species is widespread in mainland Southeast Asia, with additional records to the west (the Indian Subcontinent) and east (the Philippines Archipelago), but was previously unrecorded from the islands of the Sundas. The secretive habits of the species, including the occupancy of mud lobster (Thalassinia spp.) mounds in mostly inaccessible, swampy habitats may be a reason for its perceived rarity and few published records.